A field trial to test effects of watering, seed addition and disturbance on perennial species recruitment in Belah woodland. (19th June 2017) - Callister, Kate; Westbrooke, Martin
Summary: Failure of perennial species to regenerate is a significant threat to semi‐arid woodlands across south‐eastern Australia. High grazing pressure eliminates the recruitment of many perennial species in semi‐arid woodlands, but little is known about requirements for regeneration under low grazing pressure. We tested the effects of addition of water (irrigation to match the largest rainfall events of the last century), seed, soil disturbance and fire within a grazing exclosure in Belah ( Casuarina pauper ) woodland in the Murray‐Sunset National Park, Victoria. Recruitment was observed in 13 perennial species and was dominated by chenopods. Addition of water, seed and soil disturbance increased abundance of juvenile perennial species above the low‐level background recruitment that occurred in the prevailing drought conditions. This supports the view that continuous recruitment occurs for many semi‐arid perennials. Low seed availability and an inability to maintain soil moisture conditions matching that of regeneration events are likely factors in the lack of recruitment for tree species and limited response of shrubs in this experiment.